Aspergillus sclerotiorum: riesgo para la herencia cultural y la salud - Carrazana-García, Daymí-I; Universidad Central “Marta Abreu” de Las Villas, Santa Clara, Villa Clara, Cuba. (2014)
By performing a mycological culture, we isolated a fungal strain from a mold patch in a book of great heritage value from the “Coronado” archives. Ribosomal DNA sequencing identified the strain as Aspergillus sclerotiorum. By qualitatively determining its cellulolytic, proteolytic and amylolytic and enzymatic activities, as well as the production of pigments and acids, we confirmed its paper deteriorating abilities. Quantitatively, we evaluated its total cellulase enzyme activities on filter paper (FPase) and β-endoglucanase, and FPase and β-endoglucanase; confirming low activities. Although its deteriorating abilities are weak, it poses a threat to the preservation of the document and is a potential health hazard to the people who refer to and archive these books.